2017
DOI: 10.1371/journal.pone.0176165
|View full text |Cite
|
Sign up to set email alerts
|

Gap-crossing behavior in a standardized and a nonstandardized jumping stone configuration

Abstract: Over the last years, the omnipresent standardization of playgrounds—the distances between, for example, jumping stones tend to be equal—has been criticized by both scientists and architects. First, it has been argued that standardization fails to do justice to the variability in the children’s action capabilities. Second, it might simplify play in that children repetitively cross over the same distance and, thus, do not have to worry about their movements anymore. In the present study we examined the gap-cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Children tend to prefer spaces that afford challenges, manipulation and place-making, such as equipment for climbing, spaces for ball games, scooters, rock walls, and rocks to climb on, as well as natural elements such as flowers and green plants, and loose materials such as twigs, leaves, stones, sand, dirt, various tools, and toys [ 49 , 50 , 51 ]. Research has also found that children prefer non-standardized and more challenging play environments over safer and more standardized play environments [ 52 , 53 ]. Nevertheless, few studies have explored how children use the physical outdoor play environment to engage in different forms of risky play.…”
Section: Introductionmentioning
confidence: 99%
“…Children tend to prefer spaces that afford challenges, manipulation and place-making, such as equipment for climbing, spaces for ball games, scooters, rock walls, and rocks to climb on, as well as natural elements such as flowers and green plants, and loose materials such as twigs, leaves, stones, sand, dirt, various tools, and toys [ 49 , 50 , 51 ]. Research has also found that children prefer non-standardized and more challenging play environments over safer and more standardized play environments [ 52 , 53 ]. Nevertheless, few studies have explored how children use the physical outdoor play environment to engage in different forms of risky play.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when evaluating the variety of gap widths, both groups created an non-standardized stepping stone configuration in which the number of different gap widths did not significantly differ between the young and older adults. Such non-standardized configurations also underpin the choice for challenge, as they demand more balance control and action preparation than standardized configurations (Sporrel et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…We also examined challenge by exploring the amount of variation of the created gap widths. Arguably, a design with a great variety of gap widths is more challenging than a more predictable standardized design with equal distances, because one needs to adjust every next step when stepping from stone to stone (Sporrel et al, 2017b). We hypothesized that older adults would opt for a more standardized design than young adults, taking into account the common fear of falling and age-related declines in perception and action (Todd and Skelton, 2004;Scheffer et al, 2008;Osoba et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These authors were inspired by an earlier study that revealed that children created varying distances between jumping stones if they were the architect of their own playground (Jongeneel et al, 2015). To test whether children are more attracted to such non-standardized configurations than to the symmetrical configurations that van Eyck tended to design, Sporrel et al (unpublished) placed both configurations in a public park.…”
Section: An Ecological Approach To the Human Environmentmentioning
confidence: 99%
“…Although only 17 of his playgrounds are left today (van Lingen and Kollarova, 2016), van Eyck’s project continues to have an impact on thinking about cities, architecture, playgrounds, and children. Over the last two decades, the playgrounds of van Eyck have been honored and studied by different academic disciplines, including sociology, art, architecture, and psychology (e.g., Lefaivre and Tzonis, 1999; Fuchs, 2002; Strauven, 2002; Solomon, 2005, 2014; Sennett, 2008; Jongeneel et al, 2015; van Lingen and Kollarova, 2016; Sporrel et al, 2017; Sporrel et al, unpublished). In the present paper, we will analyze van Eyck’s playgrounds drawing upon these diverse disciplines.…”
Section: Introductionmentioning
confidence: 99%